Indium Tin Oxide Coated D-Shape Fiber as a Saturable Absorber for Generating a Dark Pulse Mode-Locked Laser*Supported by the Ministry of Education of Malaysia (Grant No. LR001A-2016A) and University of Malaya (Grant No. RP039C-18AFR). (May 2020) - Nizamani, B.; Salam, S.; Jafry, A. A. A.; Zahir, N. M.; Jurami, N.; Abdul Khudus, M. I. M.; Shuhaimi, A.; Hanafi, E.; Harun, S. W.
Abstract : A dark pulse mode-locked laser is experimentally demonstrated using the indium tin oxide (ITO) coated D-shape fiber as a saturable absorber (SA). Using the polishing wheel technique, a D-shape single mode fiber was fabricated. A 60-nm-thick layer of ITO was deposited over the D-shape fiber using the electron beam deposition method. The SA has a saturation intensity of 40.32 MW/cm 2 and a modulation depth of 3.5%. A stable dark pulse mode-locked laser was observed at a central wavelength of 1559.4 nm with repetition rate 0.98 MHz, pulse width 370 ns and signal-to-noise ratio 61 dB.